Construcciones verbales en el discurso de la genómica. Tipología verbal y discurso científico - Lorente Casafont, Mercè (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
Based on the linguistic approach of the Communicative Theory of Terminology, this paper, focuses on the semantic classification of verbs taken as a sample of the Human Genome discourse in the Spanish language, in order to describe specialized lexical units and codify verbal lemmas on computational dictionaries for specialized corpora processing and information retrieval. The semantic classifícation proposals of verbs come from Levin (1993) and the CLIPS project (ILC-CNR, Pisa).
Verbal constructions in the discourse about genomics. Verbal typology and scientific discourse